Occupational Shift in Semi-urban areas of Nepal: A Socio-cultural Dynamics - Acharya, Rakshya (Journal of Technical and Vocational Education and Training, 2022)
Occupational shift, people shifting from the traditional sector to the modern economic sector, is a global phenomenon. People in Nepal are also shifting away from agriculture to other economic sector. But in Nepal, the socio cultural dynamics is considered more vital in this shift. This paper analyzes peoples’ perception regarding their experiences of occupational shift from sociocultural perspective. This study adopts a qualitative research design with narrative inquiry approach. For this, the experience of four research participants from Kathmandu valley were purposefully selected. In addition to listening and reflecting to their life stories about engagement to abandon agriculture occupation, their activities, emotions, and lifestyle were also narrated, observed and analyzed. The findings of this research indicate that several socio cultural aspects such as modernization, urbanization, industrialization had greater influence in this process. People in the name of being modern, were gradually shifting from traditional sector (agriculture) to modern economic sectors. The research hence concludes that potentiality of agricultural sector is still high for the country to generate employment and thus it is important to redefine the agricultural policy to attract youth towards it.